Pengaruh Kompetensi SDM, Kompetensi Wirausaha, Motivasi Berwirausaha dan Niat Berwirausaha terhadap Kinerja Usaha Kain Sasirangan di Kotamadya Banjarmasin - Meiske Claudia; Marijati Sangen (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This study aims to determine and analyze the influence of HR competencies, entrepreneurial competencies, entrepreneurial motivation and entrepreneurial intentions on business performance of Sasirangan MSMEs in Banjarmasin Municipality. The research results are expected to be able to identify and produce parameters for each research variable so that it becomes the basis for further research - for the purpose of scientific development in the field of HR Entrepreneurship. Research contribution results in the sustainability of the Sasirangan MSMEs business in the Banjarmasin Municipality by giving suggestions to Sasirangan business owners in paying more attention to their HR competencies and the importance to develop their own entrepreneurial competencies. Additional sugestions given also to maintain their level of entrepreneurial motivation and intentions in order to maintain and improve their business performance sustainability. This research was conducted with a survey method using a questionnaire and structured interviews. The sample selection uses proportional simple random sampling technique. Data processing uses the help of statistical applications, descriptive analysis and multiple linier regression analysis. The results showed that only entrepreneurial competence had a significant effect on business performance of Sasirangan MSMEs in Banjarmasin Municipality. This means that the higher / better the entrepreneurial competence, the higher their business performance. Future research can add other variables that also influence the success of Sasirangan MSMEs business performance such as: capital, technology adaptation, online marketing, etc.